FINDING, ORGANIZING AND USING HEALTH INFORMATION: (2011)
This book is a product of the devotion and dedication of medical librarians in Africa for the development of a healthy society through information literacy. Information literacy has become an essential requirement in today’s world of information and technology. The web has revolutionized information retrieval and in today’s information world, the word literacy therefore goes beyond the traditional definition of knowing how to read and write. Wilson, E an American Scientist rightfully stated “we are drowning in information, while starving for wisdom. The world henceforth will be run by synthesizers, people able to put together the right information at the right time, think critically about it, and make important choices widely.” This cannot be overemphasized when it comes to health as information literacy is crucial in ensuring all those involved with health including healthcare providers, medical librarians and consumers know how to find, use and manage health information. This is due to the fact that access to right and accurate information is a prerequisite to good health. Whether you are a doctor, a nurse, an allied health professional or a medical librarian, this manual provides answers to the most crucial questions that arise while searching for health information. These questions range from: What information sources are available? What tools are available for searching the web? What techniques do you apply when searching the web? What is intellectual property right? How do you manage and store information once retrieved from the web? How do you evaluate information so as to use what is accurate? How do you use information for scholarly purposes? The authors of this manual have provided answers to these key questions so as to ensure that looking for information does not become a frustrating task and that the right information is retrieved, stored and used in an ethical manner. Having worked with health information for over 15 years I have come to recognize the challenges involved in retrieving information from the World Wide Web and more so at a time where Evidence Based Information is imperative. This manual has made great strides in trying to answer various issues surrounding information retrieval and I am without doubt that many readers will gain a lot from this invaluable resource. A lot of effort has also been made to have an all inclusive and broad manual. Ultimately, this is to serve as a guide and can be customized where necessary to match individual needs.